EVALUASI DAMPAK PROGRAM PENGEMBANGAN KAWASAN PESISIR TANGGUH (PKPT) DI DESA BEDONO KECAMATAN SAYUNG KABUPATEN DEMAK - Riskana Firdya; Kismartini Kismartini (Journal of Public Policy and Management Review, 2018)
The Tangguh Coastal Area Development Program (PKPT) is a National Community Empowerment Program for Marine and Fisheries that is regulated in the Regulation of the Minister of Marine and Fisheries No. 07 / Permen-KP / 2012. Through a qualitative descriptive approach, this study aims to evaluate the impact of the activities carried out in the program. PKPT activities consist of Human Development, Business Development, Community Development or Infrastructure and Disaster Preparedness or Climate Change. From the results of the evaluation, the outputs of the activities were the establishment of socialization of training on the development of small businesses, road construction, rehabilitation of road elevation bridges, road hardening, manufacture of bamboo taluds and concrete breakwaters. The benefit is that the community feels safe that they have not been affected by the tidal flood, the community has become enthusiastic about working and has alternative livelihoods. The impact is that the community has improved the socio-economic conditions of the community but the business development activities have no impact because the community does not want to continue the small business on the grounds that there is no business capital. The PKPT program has an inhibiting factor, namely the absence of cooperation with other agencies, difficult road access, adolescents on behalf of NGOs. This research gives recommendations that the preparation, socialization and training that is mature before the program really runs, the PKPT program needs cooperation with other agencies so that when the implementation of infrastructure development has stages in accordance with the rationality that should be, business training is needed as an alternative livelihood for the Bedono villagers. so that those who get business coaching are not just one hamlet, it requires seriousness and high commitment from all parties to synergize in building the coastal area so that the implementation is not impressed only to pursue budget absorption targets only.